Clinicopathological studies on chickens feed on some animal and non animal protein - Salem, Fakhry S.; Bader, M. O. Twfik; Abd El-Hamied, Sahar S.; Ali, Dalia T. M. (2009)
The present study was performed to investigate the clinicopathological changes associated with different protein sources. One hundred and forty, one day old Cub-500 chicks were used for this investigation. They were divided into three groups according to the ratio of protein supplemented from different sources, the first group (A) fed on com-soybean meal and was kept as control, the second one contained 40 birds and subdivided into 2 equal subgroups (B 1 and B2) each of 20 chicks fed on diet contains corn gluten meal (CGM) at levels 5% and 10%. The third group fed on animal protein diet, contained 80 birds and subdivided into 4 equal subgroups C1 and C2 fed on diet contains fish meal (FM) at levels 5% and 10% and C3 and C4 fed on diet contains meat & bone meal (MBM) at levels 5% and 10%. Blood samples were collected from wing vein under aseptic precautions at the 21 and 46 day old from 5 birds in each group for biochemical and immunological studies.
Includes references.
Summary in Arabic.
1
Keywords: Chickens -- Feeding and feeds; Chickens -- Physiology; Chickens -- Immunology; animal source protein